Timbalier Island Restoration - Anderson, Sean (California State University Channel Islands Library)
In April 1995, sand-trapping fences were built in 7 locations (totalling 7,400 linear feet) along the length of the island's beaches to trap wind-blown sand & promote sand dune formation. Dune grasses were planted behind the fences in July 1996 to stabilize trapped sand.